Neuroinflammation Upregulated Neuronal Toll-Like Receptors 2 and 4 to Drive Synucleinopathy in Neurodegeneration - Lucia Yi-Ru Chung; Yi-Ting Lin; Chi Liu; Yi-Cheng Tai; Yi-Cheng Tai; Han-Yi Lin; Chin-Hsien Lin; Ching-Chow Chen (Frontiers Media S.A., 2022)
Background: Parkinson's disease (PD) is characterized by intraneuronal α-synuclein aggregation called Lewy bodies and progressive dopaminergic neurodegeneration. Toll-like receptor (TLR) signaling is a major pathway mediating inflammation. The molecular link on how neuroinflammation upregulates neuronal TLRs and induces accumulation of α-synuclein aggregates to drive synucleinopathy remains to be determined.Objective: Despite conditioned medium from microglia and TLR agonists were utilized to study their effects on neuronal cells, a Transwell coculture system, comprising lipopolysaccharide-activated microglia on top and retinoic acid-differentiated SH-SY5Y cells at the bottom more mimicking in vivo neuroinflammation, was employed to elucidate the mechanism of activated microglia on neuronal cells.Methods: Genetic variants of TLRs in PD patients were genotyped and the multiplex cytokines, sRAGE, and HMGB1were assessed. A coculture system was employed to measure α-synuclein aggregates and neurite shortening by confocal microscope. The expression of TLR2/4 and autophagy flux was detected by western blot and immunofluorescence.Results: PD patients showed higher plasma levels of proinflammatory cytokines and genetic TLR4 variant, c.896 A > G (p. D299G). Elevated proinflammatory cytokines in coculture medium was also seen. Phosphorylation and aggregation of α-synuclein, shortening of neurite, upregulation of TLR2/4 expression, activation of downstream p38 and JNK, and dampening of autophagic flux were seen in SH-SY5Y cells cocultured with activated microglia. Those were prevented by inhibiting TLR2/4 and p38/JNK signaling.Conclusion: Activated microglia-derived neuroinflammation induced neuronal TLR2/4-p38/JNK activation to perturb autophagy, causing accumulation of α-synuclein aggregates and neurite shortening. Targeting neuronal TLR2/4 pathway might be a mechanistic-based therapy for neurodegenerative disease, such as PD.